Applied calculus for managerial, life and social sciences - Tan, Soo Tang (Brooks/Cole / Thomson, 2005)
Combining the best of traditional coverage with modern tools, market-leading APPLIED CALCULUS FOR THE MANAGERIAL, LIFE, AND SOCIAL SCIENCES: A BRIEF APPROACH, sixth Edition, applies math to your world. It delivers just the right balance of applications, pedagogy, and technology to help you succeed in the course. Teaching by application, the text is packed with real-life examples that motivate and enlighten you. Its intuitive approach introduces abstract concepts through examples drawn from common experiences to which you can relate. It also includes insight from professionals about how they integrate math into their day-to-day operations. Numerous exercises, including Diagnostic Tests, ensure you have a solid understanding of text concepts before advancing to the next topic--or exam. An exciting array of supplements--Enhanced WebAssign, Solution Videos, Personal Tutor--equips you with extensive learning support that helps maximize your study efforts and improve your grade. Eliminating the apprehension many students feel when they begin this course, APPLIED CALCULUS FOR THE MANAGERIAL, LIFE, AND SOCIAL SCIENCES: A BRIEF APPROACH, sixth Edition, uses an accessible presentation of concepts and methods that makes it an excellent resource for majors and non-majors alike.